Simulation and Analysis of Airflow for Heat Transfer from NMC Lithium-Ion Batteries in Electric Vehicles Using CFD Methods - Phosri, Rattapon; Yabsungnoen , Thammarat (Srinakharinwirot University Engineering Journal, 2025)
Electric vehicles have advanced significantly and are now widely used in daily life, with the potential to replace internal combustion engine vehicles. One of the key technologies in electric vehicles is the battery, which determines the driving range. Currently, one of the most important battery types used in electric vehicles is lithium-ion NMC due to its high energy density. However, a major drawback is that its efficiency is highly sensitive to temperature, making the design of an effective cooling system crucial. Heat is primarily generated during the charging and discharging processes of the battery. A study by Mohsen Akbarzadeh and colleagues simulated airflow and heat transfer using CFD. Their findings suggested that an airflow rate of 21 l/s combined with 5 mm air channels was sufficient to cool a system of twelve 3.7 V 43 Ah NMC battery cells, maintaining the battery temperature within an optimal operating range. This research was then applied to a system of twenty-four 3.7V 180 Ah NMC battery cells. However, CFD simulations indicated that the battery temperature exceeded the normal operating range. To address this issue, the volumetric flow rate was increased to 127 l/s, which successfully maintained the battery temperature within the optimal range. However, this resulted in a high pressure drop. Consequently, the air channel size was increased to 7 mm, reducing the pressure drop but causing the battery temperature to exceed the optimal range by 10 °C, making the setup impractical for real-world applications.